PENGEMBANGAN KARIER WANITA BERDASARKAN TEORI MOTIVASI HIRARKI KEBUTUHAN ABRAHAM MASLOW - Komalasari, Yeyen (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.09.TAHUN.2022DO - 10.24843/EEB.2022.v11.i09.p08, 2022)
This study aims to analyze the women career development based on Abraham Maslow's hierarchy of needs motivation theory. This research was conducted on female employees in the Denpasar area with a sample of 80 people using purposive sampling. Collecting data using a questionnaire. Data were analyzed using regression analysis techniques. The results of this study indicate that physiological needs, security needs, social needs, esteem needs, and self-actualization needs have a positive and significant effect either partially or simultaneously on women's career development.. Self-actualization needs most dominantly affect women's career development, then followed by social needs, esteem needs, physiological needs and the last is the need for security. Multiple determination analysis shows Abraham Maslow's hierarchy of needs motivation theory contributes 73.2% to women's career development.